Integrating climate, peace, and security in MENA Countries’ NDCs - Meddings, George; Schapendonk, Frans (2024)
The potential threat climate change poses to peace and security is perhaps nowhere more apparent than in the Middle East and North Africa (MENA). Nationally Determined Contributions (NDCs) are one way MENA countries can address this compound risk.